Use of allyl intermediates in novel synthesis of pitavastatin key heterocyclic building block: 2- cyclopropyl -4-(4-fluorophenyl)quinoline -3- carbaldehyde - Čusak, Alen; Časar, Zdenko; Jukič, Marko; Šterk, Damjan (Anali PAZU, 2022)
A key building block of pitavastatin: 2-cyclopropyl-4-(4-fluorophenyl)quinoline-3-carbaldehyde was prepared via a new synthetic method. Key feature of the presented synthetic method is introduction of an allyl group into an early -cyclopropyl substituted ketone intermediate. The latter can be cyclized with (2-aminophenyl)(4-fluorophenyl)methanone into 3-allyl-substituted kinoline. This kinoline can be transformed into title compound in 3 steps involving izomerisation of the allyl into alkene moiety, oxidation of the alkene to diol and oxidative cleavage of vicinal diol. Synthesis enables preparation of title compound in overall 14 % yield (68 % average yield per step) for un-optimized conditions by using industrially acceptable reagents and conditions.
Keywords: statins; pitavastatin; heterocycles; quinolines